201k views
0 votes
Find the zeros of the function.

Write the smaller solution first, and the larger solution second.
g (x)=(x -2)(3x +3)

Smaller x=
Larger x=

User Zerhinne
by
4.9k points

2 Answers

4 votes

Explanation:

To find the Zeros of the function we equate the function ( here g ( x ) ) by zero

=> g ( x ) = ( x - 2 ) ( 3x + 3 )

g ( x ) = 0

( x - 2 ) ( 3x + 3 ) = 0

either , ( x - 2 ) = 0 OR ( 3 x + 3 ) = 0

x = 2 OR 3x = ( - 3 )

x = 2 OR x = ( - 1 )

Smaller x = ( - 1 )

Larger x = 2

User Lokesh Sanapalli
by
5.9k points
2 votes

Answer:

see explanation

Explanation:

To find the zeros equate g(x) to zero, that is

(x - 2)(3x + 3) = 0

Equate each factor to zero and solve for x

x - 2 = 0 ⇒ x = 2

3x + 3 = 0 ( subtract 3 from both sides )

3x = - 3 ( divide both sides by 3 )

x = - 1

Hence

smaller x = - 1

larger x = 2

User Jennie Ji
by
5.1k points